163k views
5 votes
8.) Given the 2 equations below, is step 1 correct for each? If so, explain the correctmathematical procedure done to get to step 1. If step 1 is incorrect, explain what theperson did wrong.a. Equation: 4p - 5= 3(p – 3) +4 I- +Step 1: 4p - 5 = 3p-3+ 4b. Equation:4p - 5 = 3p + 1Step 1:7p - 5 = 1

1 Answer

5 votes

To answer this question we will use the distributive property:


a(c+d)=ac+ad\text{.}

Therefore:


\begin{gathered} 3(p-3)=3\cdot p+3\cdot(-3) \\ =3p-9. \end{gathered}

Now, we know that:


3p-9\\e3p-3.

Therefore step 1 is incorrect.

Step 1 is incorrect because the person did not use the distributive property properly.

Answer: Step 1 is incorrect because the person did not use the distributive property properly.


3(p-3)\\e3p-3.

User Brandon Leiran
by
4.8k points